2015
DOI: 10.1007/s13353-015-0303-8
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of chlamydia-like organisms pathogenic to fish

Abstract: Bacteria from the Chlamydiales order have been long known, especially as pathogenic bacteria to humans and many animal species, principally including birds and mammals. But for slightly over 20 years, they have been identified in the aquatic environment as endosymbionts of amoebas and sea worms. For several years, they have also been recorded as a cause of diseases among fish, causing respiratory system infections in the form of epitheliocystis of the gill. At present, 11 chlamydia-like organisms pathogenic to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 56 publications
(81 reference statements)
2
24
0
4
Order By: Relevance
“…These bacteria cause a number of important diseases like trachoma, abortions and respiratory infections (Everett et al, 1999;Horn, 2008;Soldati et al, 2004;Ossewaarde & Meijer, 1999). Till date, 11 chlamydia-like organisms have been reported to be pathogenic to fish (Pawlikowska-Warych & Deptuła, 2016). Although there are established methods for culture of Chlamydia and CLOs from humans and arthropods, it has not been possible to culture the fish chlamydial organisms (Corsaro & Greub, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…These bacteria cause a number of important diseases like trachoma, abortions and respiratory infections (Everett et al, 1999;Horn, 2008;Soldati et al, 2004;Ossewaarde & Meijer, 1999). Till date, 11 chlamydia-like organisms have been reported to be pathogenic to fish (Pawlikowska-Warych & Deptuła, 2016). Although there are established methods for culture of Chlamydia and CLOs from humans and arthropods, it has not been possible to culture the fish chlamydial organisms (Corsaro & Greub, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…(Martel et al. ; Pawlikowska‐Warych and Deptuła ), and many others. Recent reports have shown that amphibian pathogens can affect fish, such as the Ranavirus frog virus 3 (Waltzek et al.…”
Section: Discussionmentioning
confidence: 99%
“…Також було підтверджено наявність Parachlamydia acanthamoebae у вигляді змішаних інфекцій з бактеріями родини Chlamydiaceae або з іншими хламідієспорідненими організмами у жуйних. Parachlamydia acanthamoebae були виявлені в питній воді, що вказує на можливе джерело інфекції і спосіб передачі цього патогенна як тваринам, так і людині (Maurin et al, 2002;Blumer et al, 2011;Wheelhouse et al, 2012).…”
Section: плр-тест-система видової ідентифікації Parachlamydia Acanthaunclassified
“…На жаль, в арсеналі гуманної і ветеринарної медицини України не існує таких тест-систем, які б могли виявити і диференціювати хламідіє-споріднені організми, зокрема Parachlamydia acanthamoebae. Необхідність таких тест-систем обумовлена не тільки можливістю їх використання в наукових дослідженнях з метою виділення і вивчення окремих штамів, проведення епізоотичного моніторингу, а й з метою ефективного лікування, оскільки різні види мають різну чутливість або навіть нечутливість до різних видів антибіотиків (Maurin et al, 2002) та різняться джерелом збудника інфекції і шляхами його передачі. Метою нашої роботи було розробити ПЛР-тест-систему для індикації і видової диференціації Parachlamydia acanthamoebae.…”
Section: плр-тест-система видової ідентифікації Parachlamydia Acanthaunclassified